Advances in Exploring Mechanisms of Oxidative Phenolic Coupling Reactions - Choi, Haeun; Suh, Sung Eun; Kang, Houng (Advanced Synthesis and Catalysis, 2024)
Biphenolic compounds serve as important scaffolds for the development of biologically active molecules. Among the methods for the synthesis of biarenols, oxidative coupling, which directly forms a C−C bond, has been extensively explored in various metal-catalyzed (V, Cr, Co, Fe, Cu, etc.) reactions, electrochemical reactions, and photochemical reactions over the decades. While the exact mechanisms remain elusive in many cases, numerous mechanistic studies have provided valuable insights. This review focuses on the mechanistic details of the oxidative coupling of phenols or naphthols, involving at least one radical intermediate. Additionally, the factors governing chemoselectivity (homo- and cross-coupling), regioselectivity (ortho-, meta- and para−), and enantioselectivity (R and S configuration) are discussed, with a particular emphasis on intermediates and transition states, encompassing various oxidation sites for phenols and potential coupling sites.
Keywords: Asymmetric Synthesis; BINOL; Biphenol; C−C Coupling; Mechanism; Oxidative Coupling; Phenolic Coupling